Pengaruh Corporate Governance, dan Karakteristik Perusahaan Terhadap Kinerja Keuangan Perusahaan: Studi pada Perusahaan Barang Konsumen Primer Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Rini Astuti; Lukman Pakaya; Muzdalifah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to find out how much influence corporate governance and company characteristics have on the financial performance of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. Sample selection was carried out using purposive sampling to obtain eighteen companies that met the requirements as samples. The data used in this research is secondary data in the form of financial reports obtained through the Indonesia Stock Exchange (IDX) with a total of 72 financial reports observed. This research uses multiple linear regression statistical methods in the IBM SPSS Statistics 22 application. The results of this research show that: (1) corporate governance has a positive and insignificant effect on financial performance, (2) company characteristics have a positive and significant effect on the company's financial performance, and (3) simultaneously corporate and company characteristics have a positive and significant effect on the financial performance of manufacturing companies in the food and beverage sub-sector, with a coefficient of determination value of 7.9% while the remaining 92.1% is influenced by other factors not included in this research.